1978
DOI: 10.1159/000237809
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> Comparison of the Antifungal Activities of R34,000, Miconazole and Amphotericin B

Abstract: In vitro susceptibilities of 78 isolates of pathogenic filamentous fungi to the imidazole compounds R34,000 and miconazole and to amphotericin B were determined using an agar dilution technique. Allescheria boydii, Sporothrix schenckii and the dematiaceous fungi (Cladosporium, Fonsecaea and Phialophora spp.) were most susceptible to miconazole with minimum inhibitory concentration (MIC) values ranging from ≤ 0.25 to 32 µg/ml and with geometric mean MIC (G-MIC) values of 0.56–1.24 µg/ml. Isolates of Aspergillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…One previous report on the in vitro sus ceptibilities of the dematiaceous fungi av eraged the findings for 13 strains of Cladosporium, Phialophora and Fonsecaea spe cies [19]. Only 23% of the strains were sus ceptible to ^4 ¿tg/ml of Amph B; since different species of dematiaceous fungi were tested, it is not possible to make a di rect comparison.…”
Section: Discussionmentioning
confidence: 97%
“…One previous report on the in vitro sus ceptibilities of the dematiaceous fungi av eraged the findings for 13 strains of Cladosporium, Phialophora and Fonsecaea spe cies [19]. Only 23% of the strains were sus ceptible to ^4 ¿tg/ml of Amph B; since different species of dematiaceous fungi were tested, it is not possible to make a di rect comparison.…”
Section: Discussionmentioning
confidence: 97%
“…Com pounds belonging to the imidazole class o f antifungal agents have been shown to have broad spectra of antifungal activities in vitro [1,2,4,6]. Oxiconazole [Ro 13-8996; Z-2,4-dichloro-2-imidazoll-yl)-acetophenonel-0-(2,4-dichlorobenzyl)-oxime nitrate; F. H offm ann-La Roche, Basel, Switzerland; Siegfried, Zofingen, Switzerland] is a recently de scribed imidazole derivative characterized by a broad antifungal spectrum in vitro as well as in vivo activity both topically and orally [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the drug-free plates was inoculated at the beginning and the other at the end of the set. Plates were incubated at 300C for 2 May 1983). Also, it has been shown that R 51,211 has curative effects at dosages of 2.5 to 10 mg/kg in experimentally disseminated trichophytosis and systemic candidiasis (12).…”
mentioning
confidence: 99%